Study of galactic cosmic rays at high cut-off rigidity during solar cycle 23 - Chowdhury P.; Dwivedi B.N. (My University, 2025)
Galactic cosmic rays (GCRs) while propagating to and inside the heliosphere, encounter an outward moving solar wind with cyclic magnetic field fluctuation and turbulence, causing convection and diffusion in the heliosphere. Cosmic ray counts from the ground-based neutron monitors show intensity changes, which are anticorrelated with sunspot numbers with a lag of a few months. They also lose energy as they propagate towards the Earth and experience various types of modulations due to different solar activity indices. All these perturbations contribute and influence space weather and terrestrial climate. In this work, we study some aspects of the solar modulation of GCR intensity, analyzing data obtained from Beijing neutron monitor station (cut-off rigidity ∼10 GV) for the solar cycle 23 (1996-2008). We also investigate the short and mid-term periodicities of GCRs for this cycle. From the wavelet power spectrum, we find a number of short and intermediate term quasi-periodicities which also vary with time. We discuss our results in light of modulation models including drift effects.